Critical Condition for the Particle Combustion of Carbon Activated in a Hot, Quiescent Environment: Comparisons with Experimental Results. Issue 6 (3rd June 2017) - Makino, Atsushi
ABSTRACT: Appropriateness and/or usefulness of the critical condition, being derived in a previous work related to the activation of solid fuel particles, have further been examined by conducting comparisons by use of such experimental data in the literature as are reported to burn-out in a quiescent environment. Results of various carbonaceous solid fuels used are those from anthracite to low-rank coal char, as well as petroleum coke, after confirming kinetic parameters for the surface reaction that are indispensable in evaluating combustion rate. Particle sizes reported are those from 25 μm to 4 mm; ambient temperatures are those higher than 1300 K. Use has been made of the Arrhenius plot of the extended comprehensive parameter consisting of frequency factor of the surface C–O2 reaction, particle diameter, oxygen mass-fraction, and pressure ratio, the upper half of which, separated by the critical condition, corresponds to that for particle burn-out with the surface reaction activated. As far as the trend and approximate magnitude are concerned, a fair degree of agreement has been demonstrated, in general, suggesting that the formulation used has captured the essential feature of the particle combustion, elucidation of which has not been made by the others. In addition, once again, it has been confirmed that the reduction in particle size does not necessarily favor the particle combustion, and that the surface reaction ceases to be activated when the particle size is reduced below the critical one.